Elemen-elemen keberkesanan program pengimarahan masjid era kontemporari: kajian analisis keperluan - Mohd Suhardi, Mat Jusoh; Abdul Kamil, Jamaludin; Mohd. Nordin, Samah (Penerbit Universiti Malaysia Pahang, 2022)
In today's contemporary era, the function of the mosque should not be limited as a worship institution. In fact, the role of the mosque should be beyond the boundaries, which is the mosque should be an effective center for the development of muslim community. In this regard, a lot of efforts to strengthen the mosque programmes should be implemented consistently in order to meet the goals of the development for muslim community contemporary. In this aspect, this study seeks to identify the main elements of the effectiveness for the mosque programmes to be in line with the framework of muslim community development in the contemporary era. The methodology of this study is a content analysis through qualitative method by reviewing of previous and current studies in the same and similar study to the title of this study. Based on the findings of document analysis, researchers can identify five main elements of the effectiveness for current mosque programmes that need to be strengthened namely professional management of mosque programmes, data profiling of mosque visitors, mosque networking with government and private agencies, empowerment of non-formal education programmes, application of technology in mosque current programmes. These five elements are expected to strengthen the current programmes with high competent today.